2010
DOI: 10.1055/s-0030-1265129
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Endothelium on Adrenal Steroidogenesis and Growth are Mainly Mediated by Proteins Other than Endothelin-1

Abstract: The endothelium releases factors stimulating the adrenal cortex. It is also known that endothelin-1 (ET-1) promotes generation of cortisol and aldosterone, and proliferation of adrenocortical cells. The aim of the study was to find out whether the effect of the endothelium on adrenocortical cells is dominated by the action of ET-1. The effects of endothelial cell-conditioned medium (ECCM), obtained during growth of human umbilical cord vein endothelial cells, on aldosterone and cortisol release by cells of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…ACTH and cortisol serum concentrations were measured by radioimmunoassays (Diagnostic System Laboratories Deutschland DSL, Sinsheim, Germany) as recently described [26]. Concentrations are given as pg/ml for ACTH and μg/dl for cortisol.…”
Section: Methodsmentioning
confidence: 99%
“…ACTH and cortisol serum concentrations were measured by radioimmunoassays (Diagnostic System Laboratories Deutschland DSL, Sinsheim, Germany) as recently described [26]. Concentrations are given as pg/ml for ACTH and μg/dl for cortisol.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, endothelial cell–derived factors may synergize with angiotensin II in aldosterone induction or even sensitize mineralocorticoid cells to angiotensin II stimulation [13]. Moreover, endothelial cell–conditioned medium can stimulate proliferation of human primary normal adrenocortical and of the adrenocortical cancer cell line NCI‐H295R [14].…”
mentioning
confidence: 99%
“…For example, endothelial cell‐conditioned media are capable of stimulating the expression of aldosterone synthase as well as the promoter activity of steroidogenic acute‐regulatory protein (StAR) and thereby steroidogenesis stimulating both aldosterone and cortisol release. These endothelial effects may be in parts because of the actions of endothelial‐derived factors, such as nitric oxide or endothelin [10–14]. In addition, endothelial cell–derived factors may synergize with angiotensin II in aldosterone induction or even sensitize mineralocorticoid cells to angiotensin II stimulation [13].…”
mentioning
confidence: 99%
“…However, the current result agree with (Ansurudeen et al 2014) demonstrated that Ang II causes an increase in cortisol production. (Paramonova et al 2010) reported that ET-1 causes proliferation of adrenocortical cells and promotes cortisol secretion. Furthermore, hypercortisolemia has related with elevated ET-1 levels (Lederbogen et al 1999).…”
Section: Discussionmentioning
confidence: 99%